Computational mathematics : models, methods, and analysis with MATLAB® and MPI - White, R. E. (Robert E.) (Textbooks in mathematics (Boca Raton, Fla.), 2016)
Computational Mathematics: Models, Methods, and Analysis with MATLAB® and MPI is a unique book covering the concepts and techniques at the core of computational science. The author delivers a hands-on introduction to nonlinear, 2D, and 3D models; nonrectangular domains; systems of partial differential equations; and large algebraic problems requiring high-performance computing. The book shows how to apply a model, select a numerical method, implement computer simulations, and assess the ensuing results.